2022
DOI: 10.24815/siele.v9i1.21455
|View full text |Cite
|
Sign up to set email alerts
|

EFL teachers’ identity in self-directed learning: A work-from-home phenomenology

Abstract: Major potential effects of abrupt changes in educational settings particularly for education stakeholders such as teachers have been somewhat interesting to examine. This study examines how teachers of English as a Foreign Language (EFL) in different schooling levels acclimatize their experiences due to the unanticipated Covid-19 outbreak, which forced them to pursue Online Distance Learning (ODL). Employing a phenomenological approach, eight teachers from various educational and psychometric backgrounds in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…First, the findings revealed that the EFL students felt that the support of their families was the highest level of social support they have received; thus played a significant role in their academic success. Such finding corresponds with (Ashadi et al, 2022;Aghayani and Janfeshan, 2020;Dewi, Marlina and Supriyono, 2019;Du Toit-Brits, 2018;Dwilestari, 2021;Murniati, Hartono, and Nugroho, 2023) who found that EFL students who received social support from family members or teachers at schools exhibited high level of SDL. This type of support allow EFL students to interlink with their family members, teachers, society, and environment; thus, help the EFL shape their SDL experience, and understand the process to use acquired skills for lifetime learning.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…First, the findings revealed that the EFL students felt that the support of their families was the highest level of social support they have received; thus played a significant role in their academic success. Such finding corresponds with (Ashadi et al, 2022;Aghayani and Janfeshan, 2020;Dewi, Marlina and Supriyono, 2019;Du Toit-Brits, 2018;Dwilestari, 2021;Murniati, Hartono, and Nugroho, 2023) who found that EFL students who received social support from family members or teachers at schools exhibited high level of SDL. This type of support allow EFL students to interlink with their family members, teachers, society, and environment; thus, help the EFL shape their SDL experience, and understand the process to use acquired skills for lifetime learning.…”
Section: Discussionsupporting
confidence: 77%
“…One could argue that the strength of this study resides in the way it shows how technology can help EFL learners improve their SDL skills, which in turn helps them perform better academically and feel more confident when studying new languages. Furthermore, Ashadi et al (2022) examined the effects of EFL teachers' identity on self-directed learning. The researchers explored the working experiences from the perspective of a phenomenological approach.…”
Section: Theoretical Background and Related Studiesmentioning
confidence: 99%
“…In terms of research methods, as the review implored, we embraced, previous researchers' preferences for qualitative studies, in particular, the phenomenological approach to understanding the phenomena of reflecting on reflections (please see Amstutz, 2012;Kabilan, 2007), teacher identity (please see Ashadi et al, 2022;Goh and Matthews, 2011), and critical incident (please see Hall & Townsend, 2017;Kılıç & Cinkara, 2020) in the settings and contexts of teaching practicum (Kabilan, 2013;Kaur et al, 2021). This is because a phenomenological study is concerned with "lived experience and seeks reality in individual's narratives of their experiences of and feelings about specific phenomena, producing their in-depth descriptions" (Cilesiz, 2009, p. 240), which are very much pertinent to the elements investigated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges of current HE staff are somewhat getting more complicated to handle when ITEs encounter a situation that Ashadi et al (2022). call the unexpected transition to online distance learning or ODL.…”
Section: Introductionmentioning
confidence: 99%
“…call the unexpected transition to online distance learning or ODL. Some teachers, therefore, are generally getting lost when shifting from the traditional classroom setting to online teaching (Comas-Quinn, 2011) or confronted with perplexity and complexity due to the coercive nature of the currently existing ODL (Ashadi et al, 2022). Some investigations have put this into a focus called technology integration in online learning (Li, 2017) or teachers' technological pedagogical content knowledge (TPACK) ( (Fathi & Yousefifard, 2019;Nazari et al, 2019;Paneru, 2018), both of which enable them to open their vision and revive their teaching inventory (Pu, 2020).…”
Section: Introductionmentioning
confidence: 99%